Eritrea : Health Sector Note - World Bank (Washington, DC, 2013)
This Health Sector Note is the result of the first phase of an open, participatory three-step process for developing the Health Sector Policy and Strategic Plan (HSPSP), and serves as the preliminary basis for further rounds of discussions, and analyses among stakeholders, to arrive at a strategic vision for the national health sector. The socioeconomic situation is reviewed, stipulating Eritrea remains one of the poorest countries in the world, where lack of sustained economic growth, does not hold much promise for a reduction in poverty in the short to medium term. This will constrain growth in personal income and government revenue, and in turn, growth in domestic resources for investment in, and recurrent cost support to, the health sector. The note identifies the strengths, and challenges of the health sector, as well as the state of the human resources and infrastructure of the sector, discussing briefly, the role of the private sector. Adequate resources need to be mobilized and available to health care services, as well as to other related sectors, such as water and sanitation. However, given competing demands on the country's limited resources, actions in all sectors need to be prioritized. Recommended actions include, for the short term, the establishment of a baseline information system, so as to evaluate the performance and cost-effectiveness of specific health programs. Likewise, there is the need to estimate the National Health Accounts to better assess the sector's sources and uses of funds, and, to evaluate alternative sources of revenues, including user charges, and public and private insurance options. Medium-term priorities suggest undertaking unit costing studies to evaluate the public system's technical efficiency, to then provide a framework for a comprehensive health sector development, while long-term priorities include among others, the development of financing options for universal coverage, including public-private insurance mechanisms.